Lichen sclerosus epidemiology in girls from the Republic of Bashkortostan - L. Kh. Lukmanova; S. Yu. Muslimova; I. V. Sakhautdinova (Акушерство, гинекология и репродукция)
Aim: to study the features of lichen sclerosus (LS) epidemiology in girls from the Republic of Bashkortostan (RB).Materials and Methods. A retrospective cohort study was conducted. The authors analyzed LS incidence in girls aged 0 to 18 years, the data provided by two pediatric gynecological department, which in different years served all RB girls with gynecological pathology. A comparison of indicators recorded during the two equal and comparable time periods was carried out: the first 9 years of operation (from 1996 to 2004) at the Department of Pediatric Gynecology of the Clinical Hospital of Emergency Medical Care, Ufa and the first 9 years of operation (from 2015 to 2023) at the Gynecological Department of the Republican Children's Clinical Hospital, Ufa.Results. Lichen sclerosus in RB girls cannot be attributed to orphan disease, since its incidence rate over the past 9 years comprised 0.46 ‰, i.e., 4.6 % per 100 girls. Over the 19-year follow-up (2004–2023), the accumulated LS incidence in RB girls aged 0 to 18 years increased from 0.22 to 0.46 ‰, and in Ufa – from 0.35 to 0.65 ‰.Conclusion. In recent years, a significant increase in LS incidence in girls has been observed in the RB. Most LS patients are in the prepubertal childhood period.